Techno-Economic Evaluation of Gold Nanoparticles Using Banana Peel (Musa Paradisiaca) - Maratussolihah, Permata; Rahmadianti, Salma; Tyas, Kanthi Pawening; Girsang, Gabriela Chelvina Santiuly; Nandiyanto, Asep Bayu Dani; Bilad, Muhammad Roil (ASEAN Journal for Science and Engineering in Materials, 2022)
Biosynthesis of gold nanoparticles using banana peels is considered more economical and has been proven to produce gold nanoparticles that have various applications in the medical field. Therefore, the production of gold nanoparticles needs to be developed on an industrial scale. This paper aims to determine the feasibility of a gold nanoparticle biosynthesis project using banana peels on an industrial scale. The economic evaluation method uses an analysis of several economic evaluation parameters such as GPM (Gross Profit Margin), BEP (Break-Even Point), CNPV (Cumulative Net Present Value), PBP (Payback Period), and PI (Profitability Index). The results show that on an industrial scale, it is assumed that the amount of AuNP production in one year is 120 L. The total price required for production in one year is 3,125,204.84 USD with annual sales of 3,240,000 USD so that the total price is 114,795.16 USD per year. Under ideal conditions, the PBP analysis shows that the project will have a profit in the 3rd year, and the PI analysis shows that the initial capital costs can be covered since the 4th year. The results of the analysis in some non-ideal conditions indicate that project losses will occur. Based on the economic evaluation, it can be concluded that the production of industrial-scale gold nanoparticles by biosynthetic methods using banana peels can be carried out with anticipation of losses that will occur due to changes in some ideal conditions.